Duke Ferdinand: patient or possessed? The reflection of contemporary medical discourse in John Webster's The Duchess of Malfi. Issue 1 (21st June 2010) - Tullo, Ellen
Abstract : The Duchess of Malfi, a tragedy written by John Webster, makes frequent reference to contemporary Jacobean concerns about health and disease for dramatic effect. Most notably Webster chooses to highlight lycanthropy through the evolution of the condition in the character of Duke Ferdinand. This paper examines Webster's knowledge of contemporary medical, religious and political texts and explores the reflection of both a natural humoral understanding of lycanthropy as a disease, and the concurrent importance of supernatural concerns prevalent at the time. Although Webster's choice to associate Duke Ferdinand with lycanthropy primarily serves a dramatic purpose, it is proposed that fictional works such as The Duchess of Malfi can be considered as important sources for the history of medicine since authors often reflect the contemporary understanding of health and disease from the world around them.